TOPICS ON MUSIC PRICING: EXAMINING THE HIGH COST OF LIBRARY EBOOKS. - BERNDT, ELIZABETH (Notes, 2025)
The article "Topics on Music Pricing: Examining the High Cost of Library Ebooks" by Elizabeth Berndt discusses the financial implications for libraries in maintaining collections of music monographs in both print and electronic formats. It highlights the increased cost of maintaining contemporary collections and the rise of ebooks in academic libraries, outselling physical books since 2017. The article provides pricing examples for different ebook licenses and formats, emphasizing the challenges libraries face in balancing budgets while meeting the growing demand for digital content. It suggests exploring alternative purchasing models and advocating for policy changes to address the affordability and accessibility of ebooks in library collections.